Marek's Disease in an Indian Peafowl (Pavo cristatus) with Clinical Ocular Disease and Paraparesis. (July 2022) - Wilson, Liam A.; Lewis, Martyn; Baigent, Susan J.; Abate, Valerie; Dolega, Brooke A.; Morrison, Linda R.; Poulos, Christopher; Walker, David
Summary: Marek's disease (MD) is caused by virulent strains of Gallid alphaherpesvirus type 2 (MD virus serotype 1; MDV 1) and frequently causes a lymphoproliferative disorder in poultry and other galliform birds worldwide. However, within the peafowl (Phasianinae) subfamily, there are only rare confirmed reports of MD. Here we report MD in an Indian peafowl ( Pavo cristatus ), which clinically presented with hindlimb paraparesis and intraocular swelling of the right eye. Soft, off-white to tan masses within the right eye, sciatic nerves and coelomic cavity were identified at post-mortem examination which effaced the cranial pole of the kidneys and diffusely effaced the testes. Lymphoid neoplasia was identified histologically at all of these sites and there was extensive hepatic lymphoid cell infiltration, which had not been grossly evident. The T-cell origin of the lymphoid cells was confirmed by immunohistochemistry for CD3 antigen. A virulent strain of MDV 1 was detected by real-time polymerase chain reaction in DNA samples extracted from the kidney and testes. As MD is rare in peafowl it should be considered as a differential diagnosis for intraocular and coelomic masses with associated clinical signs.